THE DIVERSITY OF AQUATIC FAUNA SPECIES OF MANGROVE ECOSYSTEM IN GAMPONG LAMBARO SKEP KUTA ALAM BANDA ACEH - Ulia Hanum; Aja Riska (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2024)
Gampong Lambaro Skep is one of the villages in Kuta Alam district in Banda Aceh which has a mangrove ecosystem. Aquatic fauna community is one of the significant components of mangrove forest ecosystem. In order to fill the availability of biodiversity data which is basic prerequisite for developing knowledge and utilizing biodiversity in Aceh, accordingly research was conducted on the Diversity of Aquatic Fauna Species of Mangrove Ecosystem in Gampong Lambaro Skep Kuta Alam, Banda Aceh. The objective of this research is to determine the species richness and the level of diversity of aquatic fauna in the mangrove ecosystem in Gampong Lambaro Skep Kuta Alam, Banda Aceh. Samples were collected using the quadrate sampling method with destructive sampling techniques for aquatic fauna that occupy muddy mud or sand substrates. Meanwhile, samples for aquatic fauna that occupy hard substrates such as roots and trunks of mangrove trees were collected using the quadrat sampling method with a non-destructive sampling technique. Samples for aquatic fauna that occupy water column were collected with the exploring method using fishing nets. Data were analysed using the Shannon-Wiener diversity index. The results of the research show that there are 11 Species of aquatic fauna in the mangrove ecosystem in Gampong Lambaro Skep Kuta Alam, Banda Aceh. The level of diversity of aquatic fauna species in the mangrove ecosystem in Gampong Lambaro Skep Kuta Alam Banda Aceh is classified as moderate (H'= 2.058).